A secure and lightweight anonymous mutual authentication scheme for wearable devices in Medical Internet of Things. (August 2022) - Gupta, Ankur; Tripathi, Meenakshi; Muhuri, Samya; Singal, Gaurav; Kumar, Neeraj
Abstract: Medical Internet of Things (MIoT) is an emerging area of IoT comprising of wearable sensor nodes having low-powered processors. Wearable nodes gather the physiological data of a patient and transmit this real-time information to the user over an insecure channel. There is a possibility that an attacker might gather the personal or medical information of a user that has been communicated over an insecure channel. Hence, security and privacy become a major concern in MIoT for a user in the last decade. To access the medical data in the resource-constraint environment, in the current manuscript, we propose a secure and lightweight anonymous mutual authentication scheme. Our scheme works utilizing only the basic symmetric cryptosystem techniques that include cryptographic hash functions in one direction and bitwise XOR operation. As a result, the proposed framework is lightweight and also efficient than the state-of-the-art. We have validated our proposed scheme based on BAN-Logic and shown the efficiency concerning functionality, storage requirements, computation complexity, and communication costs.